“Costos por Procesos de Producción y su Incidencia en la Rentabilidad en la Avícola Imperial del Cantón La Maná Provincia de Cotopaxi Periodo 2020” - Santacruz Sanchez, Evelyn Gricelda (2021)
The production process has fundamental characteristics that allow understanding its origin and the different procedures that carry the economic resources for different companies, hence its importance to implement measures and have tools that allow organizations, specifically credit institutions, to detect any irregularities that put at risk at the time of the production process. Due to the aforementioned antecedents, it was considered feasible to implement a cost manual for production processes using the documentary, descriptive, explanatory methodology and the analytical, systematic, deductive methods. The field research was also used to collect information in the “Imperial” poultry facilities, the bibliographic research for the actual support of the theoretical information for its respective analysis, in accordance with the laws established with the regulatory entities on production. Through the diagnosis raised the current state of the poultry farm through interviews and surveys of employees and manager, it is determined that it does not have adequate control and procedures of the production processes, due to the absence of guidelines, which could lead to non-compliance of the accounting regulations, for which a manual was designed that included instructions for each process of raising chickens, mentioning each process and responsibilities they have for compliance, this manual will help companies dedicated to poultry production to keep an adequate control when producing chickens, this manual will directly benefit the directors, employees, partners and the population of La Maná canton.